El entorno familiar y su incidencia en el aprendizaje de los niños y niñas de primer año de educación básica del jardín de infantes Lucía Albán de Romero, de la ciudad de Quito. Periodo lectivo 2012-2013 - Cabrera Ureña, Dolores (2014)
This research refers to " FAMILY ENVIRONMENT AND ITS IMPACT ON LEARNING CHILDREN FIRST YEAR BASIC EDUCATION KINDERGARTEN " ALBAN DE LUCIA ROMERO " QUITO CITY school period 2012 - 2013 " that was structured and developed in accordance with the regulations in force graduation from the National University of Loja. The overall objective was formulated : To determine the impact of the Family Environment in Learning children First-Year Basic Education Kindergarten " Alban Lucia Romero" of the city of Quito. Teaching period 2012-2013. The methods used were : The Scientific Method , Inductive - Deductive , Analytic - Synthetic and Statistical Model , in order to relate the Family Learning Environment with children First-Year Basic Education , the techniques were applied following : a survey of parents to Identify types family environment in which children live , the Adaptation Test Basics " REEA " Learning to assess With the implementation of the survey of parents found that 50% of parents say the most appropriate type of Family environment is stable , 21% permissive , democratic 17% , 8% the authoritarian and 4% overprotective. The family is the first educational institution , its average in Learning and development of its members , this dynamic is who should provide the conditions to potentiate learning, so as to facilitate the social integration of their children in school . With the implementation of the Basic Functions Test Adaptation " REEA " was demonstrated that 94 % of boys and girls surveyed scored 50 % positive responses equivalent to satisfactory , 12% between 25 and 50 % positive responses equivalent to unsatisfactory , and 6% between 0 and 25 % positive responses equivalent to unsatisfactory. 71% of boys and girls surveyed have between 0 and 25 % of negative responses equivalent to satisfactory , 24% between 25 and 50 % of negative answers unsatisfactory equivalent to 12% and 50% of negative responses equivalent to satisfying. It is the family who will provide the necessary for their children to be educated and benefit from the learning process conditions. Consequently it is determined that the learning of the children in the first year of basic education in kindergarten " Alban Lucia Romero " is in relation to the Family environment in which they operate .